2016
DOI: 10.1080/21645515.2016.1151588
|View full text |Cite
|
Sign up to set email alerts
|

HPV vaccine acceptability in HIV-infected and HIV negative men who have sex with men (MSM) in Ireland

Abstract: Background Men who have sex with men (MSM), particularly HIV-infected MSM are disproportionately affected by HPV infection and associated disease. The HPV vaccine has potential to greatly reduce the burden of HPV-associated disease including anal cancer in MSM. The efficacy of the HPV vaccine is dependent on high levels of vaccine uptake. The aim of this study was to examine HPV vaccine acceptability and factors influencing vaccine acceptability in MSM in Ireland. Methods A self-administered survey was distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
4
11
0
Order By: Relevance
“…In the present study, correlates of HPV vaccine acceptability were generally consistent with those identified in several previous studies 33,34 . The men who paid more attention to their own health and who believed that HPV vaccine could effectively protect from infection had stronger willingness to get vaccinated.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, correlates of HPV vaccine acceptability were generally consistent with those identified in several previous studies 33,34 . The men who paid more attention to their own health and who believed that HPV vaccine could effectively protect from infection had stronger willingness to get vaccinated.…”
Section: Discussionsupporting
confidence: 91%
“…Concerns about the safety of HPV vaccination and potential long-or short-term side effects were reported by an average of 43% of hesitant study participants. [23][24][25][26][27][28][29]31,32,[34][35][36][37][38]40,42,46,49,[70][71][72][73][74][75][76][77][78][79][80][81] Fear of side effects was reported by an average of 52% of general study participants 51,[82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] and 17% of favourable study participants. 25,37,71 Concerns about si...…”
Section: Quantitative Resultsmentioning
confidence: 99%
“…In quantitative studies, cost was raised as an issue by an average of 32% of hesitant participants, 31,38,74,75,80 particularly in studies in Denmark (2009, 62%) 80 and Greece (2008-2014, 54%), 31 and was also raised as a concern for an average of 47% of general study participants in Germany, Greece, Hungary, Ireland, and Sweden. 46,47,94,97,120 The inconvenience of receiving multiple doses was reported by 56% of general participants in studies in Sweden (2007-2013), 96,110 25% of hesitant participants in studies in France (2015) 74 and the UK (2007-2008), 71 and 10% of favourable participants in a study in the UK (2007)(2008). 71 Increased workload created by administering the vaccine was raised as a barrier by general school nurses in a study in Sweden (2013, 40%), 110 while general adolescents in studies in Germany (2010, 12%) 95 and Greece (2008-2014, 1%) 31 reported being too busy to get vaccinated.…”
Section: Quantitative Resultsmentioning
confidence: 99%
“…The current results suggest that the MSM population in Urumqi, China has poor knowledge of HPV, at levels relatively lower than expected compared to global data previously reported in a 2014 systematic review and other studies conducted out of China. 22,29 Although the proportion of individuals who were aware of HPV is higher among HIV-infected MSM than that of HIV-uninfected, among those who knew about HPV, HIV-uninfected had a greater correct responses rate to further survey items than HIV-infected individuals. More generally the findings of these study clearly indicate that improvement of HPV knowledge of transmission, risk factors and prevention among MSM especially high-risk MSM in Urumqi.…”
Section: Discussionmentioning
confidence: 99%